Towards a Communist Armed Conflict Indigenous Settlement Framework: Revisiting Vietnam, Singapore, and Taiwan Experience - Jasmin, Jose Mari (Journal of Interdisciplinary Perspectives, 2024)
Armed conflicts between governments and indigenous inhabitants in Singapore, Taiwan, and Vietnam have deep roots in historical tensions and the marginalization of minority groups. This qualitative study explores these factors and evaluates government strategies for conflict resolution, focusing on disparities in settlement, education, employment, and community engagement. Government actions such as military operations, peacebuilding, and comprehensive programs were analyzed. Singapore's strategies, including community engagement and socio-economic development, fostered stability and inclusivity. Taiwan's reconciliation efforts, including apologies and democratization, reduced conflict and promoted indigenous rights. Vietnam's initiatives for ethnic minority development underscored its commitment to peace through inclusive approaches. Historical contexts in these countries, marked by ethnic tensions, colonial legacies, and ideological divisions, shaped significant violence and social divisions, necessitating robust security measures and reconciliation efforts. Lessons learned emphasize diplomacy, international cooperation, and socio-economic integration for lasting peace. Governments must prioritize dialogue, inclusive policies, and sustainable development supported by international partnerships. Effective conflict resolution integrates socioeconomic development and reconciliation efforts, crucial for building resilient societies and fostering peace among Indigenous populations.